Antibiotic sensitivity and pathogenicity of Aeromonas veronii isolated from diseased red hybrid tilapia in Malaysia - Bidin, Nor Roshazmin; Azmai, Mohammad Noor Amal; Mohamad, Nurliyana; Salleh, Annas; Md Yasin, Ina Salwany; Nasruddin, Nurrul Shaqinah; Saad, Mohd Zamri (Universiti Putra Malaysia Press, 2019)
This article reports the antibiotics sensitivity and pathogenicity of Aeromonas veronii 5L isolated from diseased red hybrid tilapia. The antibiotic sensitivity of A. veronii 5L was determined towards 13 antimicrobial agents. Then, the bacterial inoculums ranging between 0 and 106 CFU/mL were used for intraperitoneal challenge in red hybrid tilapia juveniles. Aeromonas veronii 5L showed resistance to ampicillin, streptomycin and sulfamethoxazole/trimethoprim. Following intraperitoneal exposure, mortality was observed as early as 24 h post infection leading to a total of 56.7% cumulative mortality at 102 CFU/mL, and 66.7% from 103 to 106 CFU/mL. Clinical signs and gross lesions including abdominal distension, detachment of scales and ulceration on the body surface, inflammation around the operculum and based of fins, hemorrhage of internal organs, and accumulation of fluid in abdominal cavity. Histopathological examinations revealed generalized congestion of the brain, necrotic hepatocytes, generalized tubular necrosis of kidney and multifocal necrosis of spleen with splenic infarction. The LD50-336h of A. veronii 5L was determined at 1.9 x 103.73CFU/mL. This study revealed the capability of A. veronii as another important pathogen in tilapia culture in Malaysia.